DAMPAK KERJA SAMA PRANCIS DAN JEPANG DALAM KERANGKA ECONOMIC PARTNERSHIP AGREEMENT (EPA) TERHADAP EKSPOR WINE PRANCIS KE JEPANG TAHUN 2018 - 2021 - Ramadhan, Agung; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
French wine exports to Japan exemplify international relations that blend Western and Eastern cultures. France's prominence as a grape cultivation center has attracted consumers worldwide, including those in Japan. However, the distribution of French wine to Japan often encounters obstacles and challenges, such as high import duties, strict regulations, and complex distribution networks. To address these issues, the Economic Partnership Agreement (EPA) was established, encompassing various provisions to liberalize trade and resolve both tariff and non-tariff barriers. On February 1, 2019, the EPA officially went into effect. This research was conducted using qualitative methods and data collection techniques, primarily through literature studies and official documents from European Union and Japanese government websites. The documents used as references in this research are official documents related to the EPA. This study applies a liberalism perspective, presented in a descriptive and explanatory manner at the nation-state level of analysis, with France as the unit of analysis. The EPA agreement between the European Union and Japan has proven to have a positive impact on French wine exports to Japan in 2018 - 2021. The result is that since the implementation of the EPA and the elimination of tariffs, there has been a decrease of – 11.45% in 2020 due to Covid-19 and the highest increase of 16 .15% in 2021. Keywords: EPA, Wine Export, Liberalism Perspective